Copyright Protection in Indonesia: Study of Amendment of Act Number 28 of 2014 on Copyright - Putranti, Deslaely (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2018)
The presence of intellectual work as the result of human ability, need to be protected in order to get recognition, appreciated and respected. The amendment to the Copyright Act Number 19 of 2002 is deemed necessary by the Government to provide better protection to the Author and the Owner of the Neighboring Rights. Based on the explanation above it can be drawn the problem formulation ie (1) How Act Number 28 of 2014 related to Copyright (New Copyright Act) regulate Copyrights and Neighboring Rights? (2) How will the Act Number 28 of 2014 related to Copyright (New Copyright Act) protect the Author and the Owner of Neighboring Rights in Indonesia? While the objective of the study ie (1) To review the regulation related to Copyright and Neighboring Rights in the new Copyright Act, (2) To review the form and substance of copyright protection to the Author and the owner of the neighboring rights in Indonesia in accordance with the new Copyright Act. This study is a normative juridical which used literature as the main foundation. The legal materials used in this study are primary legal materials which include the Civil Code and related legislation. Secondary legal materials consist of literature books, journals, and articles are used to describe the primary legal materials. The study found that (1) Act Number 28 of 2014 on Copyright accommodates the interests of the Author and the Owner of the Related Rights by providing better protection in its Articles, and (2) Some crucial changes related to Economic Rights and the change of Criminal offense to Complaint offense gives more protection to the Author and Related Rightsâ Owner.